Somatic embryogenesis and plant regeneration from callus cultures of Cleome rosea Vahl - Simões,Claudia (2010)
This paper describes a protocol for the efficient vegetative propagation of Cleome rosea by somatic embryogenesis. Leaf and stem explants from nursery-grown seedlings of C. rosea were cultivated on Murashige and Skoog (MS) medium supplemented with indole-3-acetic acid (IAA), a -naphthaleneacetic acid (NAA), 4-amino-3,5,6-trichloropicolinic acid (picloram) or 2,4-dichlorophenoxyacetic acid (2,4-D). Nodular calli were produced from both explant types in the presence of 4.5 and 9.0 µM 2,4-D. Embryo development and maturation were achieved when calli from stem explants were transferred to media containing a ten-fold reduction of 2,4-D concentration initially used (0.45 and 0.90 µM). Leaf-derived calli did not form embryos with the same treatments. The highest frequency of embryogenic callus formation (85%) and number of embryo per callus (13.45 ± 2.8) were achieved during the first subculture on medium supplemented with 0.90 µM 2,4-D. Embryo conversion into plantlets was achieved following transfer to growth regulator-free MS medium solidified with 2 g.L-1 phytagel. An acclimatization rate of 53% was found three months after transfer to ex vitro conditions and the recovered plants presented a normal phenotypic aspect.